Perbedaan Tingkat Pengetahuan Rabies Pada Kader Posyandu Yang Di Berikan Pendidikan Kesehatan Dengan Metode Ceramah Dan Leaflet Di Kabupaten Sintang, Kalimantan Barat - Retno Bintari, Adjeng (2016)
Background. Health education is important to support health programs and influences behavior as an intermediate impact result, therefore, it will increase the indicator of people's healthas an outcome of health education. The Objective of Research. This research aimed at analyzing whether there is difference in knowledge level on rabies on the cadres of Posyandu (Pos Pelayanan Terpadu/Village Integrated Health Post) who were given with health education through lecture and leaflet method in Sintang Regency, West Kalimantan. Method. This research used a research design which is a type of experimental research with the design of Quasi Experiment. 40 posyandu cadres were taken for lecture group and 40 posyandu cadres were taken for leaflet group using the technique of purposive sampling. The statistic test used is unpaired t-test. Results. This research showed that there is difference in knowledge between the lecture group and leaflet group, for knowledge on rabies using leaflet method, it was found average as much as 12.60, meanwhile, by using the lecture method is as much as 11.73. Therefore, It can be concluded that the score average of knowledge on rabies is higher using the leaflet method than the one using the lecture method. The value of p (sig) is as much as 0.043 or p < 0.05. Conclusion. Based on the findings of research, it can be concluded that there is significant difference in the knowledge level on rabies between the posyandu cadres who were given with the health education through the lecture method and the posyandu cadres who were given with the health education through the lecture and leaflet method in Sintang Regency, West Kalimantan, with the result that the knowledge level for the leaflet method is higher than the knowledge level for the lecture method with the average difference of the both methods is 0.87 that statistically means p = 0.043.